2013
DOI: 10.1021/op400129n
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Reaction and Crystallization and the Impact on Filtration, Drying, and Dissolution Behaviors: The Study of Acetaminophen (Paracetamol) by In-Process Controls

Abstract: Acetaminophen was synthesized by reacting p-aminophenol with acetic anhydride. Overall materials balance was compiled. Three different crystallization paths (i.e., cases I, II, and III) involving various modes in agitation and addition of sodium hydroxide were taken to produce acetaminophen particles with different particle size distributions (PSDs) and polymorphism. The concentration profile of acetaminophen, temperature, and pH values throughout reaction and crystallization were monitored mainly by in-proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…Since it was first synthesized by Morse in 1878, the method of paracetamol production has gone through changes in order to enhance its productivity and properties. For example, acetaminophen can be synthesized from 4- hydroxyacetophenone, nitrobenzene, 4-nitrophenol, and 4-amniophenol. , The one-step acylation of 4-aminophenol has attracted increasing attention because of its simple operating conditions, and paracetamol crystals are normally separated and purified via a recrystallization process. , Extensive work on the recrystallization of paracetamol has previously been reported using cooling and antisolvent means. Once again, there are few studies in the literature on reactive crystallization in a continuous process. The closest one is the work by Agnew et al, , who reported selective access to produce a metastable solid form of paracetamol in a COBR by adding metacetamol as a template molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first synthesized by Morse in 1878, the method of paracetamol production has gone through changes in order to enhance its productivity and properties. For example, acetaminophen can be synthesized from 4- hydroxyacetophenone, nitrobenzene, 4-nitrophenol, and 4-amniophenol. , The one-step acylation of 4-aminophenol has attracted increasing attention because of its simple operating conditions, and paracetamol crystals are normally separated and purified via a recrystallization process. , Extensive work on the recrystallization of paracetamol has previously been reported using cooling and antisolvent means. Once again, there are few studies in the literature on reactive crystallization in a continuous process. The closest one is the work by Agnew et al, , who reported selective access to produce a metastable solid form of paracetamol in a COBR by adding metacetamol as a template molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Strategically, the two separate events of crystallization and SA can be orchestrated to tune the majority of round granules to fall mainly in the range of 250–2000 μm at will which is difficult to achieve by conventional methods, such as seeding, within a reasonable batch time. The absence of filtration and drying steps between the nonstop action of crystallization and SA steps during the three-in-one intensified process also allows the favorable production of small sized crystals in the crystallization step without worrying that they would create any high wet cake resistance in filtration or powder lumping in drying, which usually take place after the crystallization step . In the three-in-one intensified process, the reaction conversion, crystal yield, agglomerate yield, the purity levels in the solution and solid phase, granular flowability, friability, strength, tabletability, and dissolution rate will be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of filtration and drying steps between the nonstop action of crystallization and SA steps during the three-in-one intensified process also allows the favorable production of small sized crystals in the crystallization step without worrying that they would create any high wet cake resistance in filtration or powder lumping in drying, which usually take place after the crystallization step. 33 In the three-inone intensified process, the reaction conversion, crystal yield, agglomerate yield, the purity levels in the solution and solid phase, granular flowability, friability, strength, tabletability, and dissolution rate will be fully investigated. Finally, to pave the way for scaling up the three-in-one intensified process for dimethyl fumarate in the future, a 10 L sized vessel will be used to prove the feasibility as well.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal‐habit modification has been investigated in the light of influencing the purification behavior , compressibility, and cake resistance during filtration and drying , , cohesion of powders , behavior during jet milling , as well as during extrusion processes , tableting behavior , , and finally wettability and dissolution rates .…”
Section: Introductionmentioning
confidence: 99%